2018
DOI: 10.2528/pierm18021604
|View full text |Cite
|
Sign up to set email alerts
|

Thinning a Subset of Selected Elements for Null Steering Using Binary Genetic Algorithm

Abstract: Abstract-Generally, the null steering is performed by controlling the amplitude and/or phase weightings of all element excitations or only a small number of them. In such cases, a need for extra RF components such as variable attenuators and variable phase shifters with each element in the array is inevitable. In this paper, an alternative method is introduced where the null steering is performed by thinning (or turning off) only a small subset of the elements in the uniform linear arrays. To find an optimum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…As we have shown in the previous section, the practical implementation of the feeding network in the electronically null steering methods is a real challenging issue, especially when dealing with large arrays. To solve this problem, many researchers, for example, see [22][23][24][25][26], proposed to mechanically control the spacing between the array elements instead of electronically controlling the amplitude and/ or phase excitations to achieve the required null steering. However, in practice, these fully nonuniform spaced arrays have also some disadvantages and difficulties to build.…”
Section: Mechanical Null Steering Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As we have shown in the previous section, the practical implementation of the feeding network in the electronically null steering methods is a real challenging issue, especially when dealing with large arrays. To solve this problem, many researchers, for example, see [22][23][24][25][26], proposed to mechanically control the spacing between the array elements instead of electronically controlling the amplitude and/ or phase excitations to achieve the required null steering. However, in practice, these fully nonuniform spaced arrays have also some disadvantages and difficulties to build.…”
Section: Mechanical Null Steering Methodsmentioning
confidence: 99%
“…To overcome these problems and make them more amendable in practice, some researchers, for example, see [22][23][24][25], have found that the required nulls can be introduced by controlling the positions of only selected elements rather than controlling the positions of all elements.…”
Section: Mechanical Null Steering Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, null steering can be achieved by controlling the amplitude-only weighting [1][2][3][4], phase-only weighting [5][6][7][8][9][10][11][12], and complex (both amplitude and phase) weighting [13][14][15][16][17][18] of array elements excitations. It can also be achieved by controlling the separation distances between array elements [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…By properly controlling the design parameters of the antenna arrays, it is possible to generate the desired radiation characteristics such as higher directivity and lower sidelobe level. The most design parameters that have been given an increased attention for many practical applications are the amplitude and the phase excitations of the individual elements [1][2][3] in addition to the element's spacing [4,5]. However, the practical implementation of the feeding networks in such arrays is known to be very complex and expensive.…”
Section: Introductionmentioning
confidence: 99%